Radar backscattering from a large-grain cometary coma: numerical simulation - Dogra, Shraddha; Grynko, Yevgen; Zubko, Evgenij; Förstner, Jens (Astronomy & Astrophysics)
We numerically simulate the circular polarization ratio of the radar signal backscattered from a large-grain cometary coma and compare the simulation results with the radar measurements for seven comets. We apply the discrete dipole approximation method and a model of random irregular particles. Our results confirm water ice composition of the cm-sized chunks detected by the NASA Deep Impact space probe in the vicinity of the nucleus of Comet 103P/Hartley 2. The index of the power-law size distribution in this case can be constrained to the range n ≈ 3.3–4.3. For the other considered comets the circular polarization ratio can be reproduced with variations of the power index between 2 and 5.
Keywords: tet_topic_scattering